Pengembangan Multimedia Pembelajaran Fisika Menggunakan Swish Max 4.0 pada Materi Cahaya Kelas VIII Madrasah Tsanawiyah - sari, ayu permata; aswirna, prima; nurhasnah, nurhasnah (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
Physics has an abstract concept and is not easily attributed to everyday events in human life, making it difficult to imagine. If the physical phenomenon being discussed has ever been experienced by learners may learners will be able to reconstruct it back into a better understanding and vice versa. Efforts to overcome every  problem  in  physics  learning  along   with  changes  in  educational communication technology in the form of utilization of learning media using a computer one of them using software swish max 4.0. The purpose of this research is to develop physics learning multimedia using swish max 4.0 on class VIII Madrasah Tsanawiyah materi cahaya  that is valid, practical and effective. The benefits of physics learning multimedia developed is as a medium of learning for educators in delivering related material, and can help in creating a fun learning atmosphere and increase learning interests of learners. Research and development using 4-D model, starting from define, design, development and disseminate. Test the  validity  of  multimedia  physics  learning  using  validity  questionnaires, practicality  test  using  questionnaire  of  practice  and  effectiveness  test  using effectiveness questionnaire. The results showed that physics learning using swish max 4.0 in materi cahaya class  VIII MTsN Durian Tarung Padang very valid, very practical and effective.